Gossypol from Cottonseeds Ameliorates Glucose Uptake by Mimicking Insulin Signaling and Improves Glucose Homeostasis in Mice with Streptozotocin-Induced Diabetes. (28th October 2018) - Alam, Md Badrul; An, Hongyan; Ra, Jeong-Sic; Lim, Ji-young; Lee, Seung-Hyun; Yoo, Chi-Yeol; Lee, Sang-Han
Abstract : Glucose absorption from the gut and glucose uptake into muscles are vital for the regulation of glucose homeostasis. In the current study, we determined if gossypol (GSP) reduces postprandial hyperglycemia or enhances glucose uptake; we also investigated the molecular mechanisms underlying those processes in vitro and in vivo . GSP strongly and concentration dependently inhibited α -glucosidase by functioning as a competitive inhibitor with IC50 value of 0.67 ± 0.44. GSP activated the insulin receptor substrate 1 (IRS-1)/protein kinase B (Akt) signaling pathways and enhanced glucose uptake through the translocation of glucose transporter 4 (GLUT4) into plasma membrane in C2C12 myotubes. Pretreatment with a specific inhibitor attenuated the in vitro effects of GSP. We used a streptozotocin-induced diabetic mouse model to assess the antidiabetic potential of GSP. Consistent with the in vitro study, a higher dose of GSP (2.5 mg/kg −1 ) dramatically decreased the postprandial blood glucose levels associated with the upregulated expressions of GLUT4 and the IRS-1/Akt-mediated signaling cascade in skeletal muscle. GSP treatment also significantly boosted antioxidant enzyme expression and mitigated gluconeogenesis in the liver. Collectively, these data imply that GSP has the potential in managing and preventing diabetes by ameliorating glucose uptake and improving glucose homeostasis.